One Path or Several? Understanding the Varied Development of Tripartism in New European Capitalisms - Sabina Avdagic (Max Planck Institute for the Study of Societies, 2006)
Are newly established institutions capable of shaping actors' strategies and coordinating behavior on a single path? Contrary to punctuated equilibrium analyses, this paper suggests that the constraining capacity of a range of newly established institutions in new European capitalisms is weak and that their very interpretation is subject to contention. Focusing on peak-level tripartism - a formally similar institution whose functioning has varied across national contexts - this paper proposes an actor-centered framework to elucidate the logic and consequences of actors? ongoing strategic maneuvering for the interpretation, enactment, and development of these young institutions. Combining insights of rational choice and historical institutionalism, the paper develops a heuristic model which, by focusing on strategic choices of government offi cials and union leaders, links the varied enactment of tripartism to different power balances that become mutually accepted in the course of their repeated interactions. In offering a set of falsifiable propositions, the paper provides a guideline for building analytical narratives to evaluate empirically this model. – – Sind neu geschaffene Institutionen in der Lage, Akteurstrategien zu determinieren? Der Ansatz dieses Discussion Papers steht im Gegensatz zu 'Punctuated-Equilibrium'-Ansätzen. Es wird argumentiert, dass in den neuen osteuropäischen Marktwirtschaften der Einfluss einiger neu geschaffener Institutionen schwach und ihre Interpretation strittig ist. Im Fokus der Betrachtung steht dabei der Tripartismus auf zentraler Ebene - eine Institution, die in verschiedenen nationalen Kontexten unterschiedliche Funktionen entwickelt hat. Von einem akteurzentrierten Ansatz aus werden Logik und Konsequenzen des permanenten strategischen Manövrierens der Akteure für die Interpretation, Inkraftsetzung und Entwicklung dieser jungen Institutionen untersucht. Das Paper kombiniert Erkenntnisse des "Rational-Choice"-Institutionalismus und des historischen Institutionalismus und entwickelt daraus ein heuristisches Modell, das - durch Fokussierung auf die strategischen Entscheidungen von Regierungsbeamten und Gewerkschaftsführern - die unterschiedlichen Inkraftsetzungen des Tripartismus mit unterschiedlichen Kräfteverhältnissen in Verbindung setzt. Diese wiederum werden im Zuge ihrer wiederholten Interaktionen gegenseitig anerkannt. Das Paper stellt eine Reihe falsifizierbarer Hypothesen auf, die Anhaltspunkte für 'Analytical Narratives' bieten, anhand derer das Modell empirisch bewertet werden kann.
Keywords: 300